Seeking the Subaltern Consciousness in Nepali Cinema - Shrestha, Tara Lal; Shrestha, Bidhya; Senehang, Dipankar; Timsina, Bibechana Sharma; B.K., Pradeep (JODEM: Journal of Language and Literature, 2021)
This article overviews the resistance of the subaltern and the ongoing debate on seeking the subaltern consciousness within and outside the elitist structure. The first part of this article exposes the notion of subaltern and subaltern resistance consciousness concerning the development of the Nepali film industry. The second part discusses different dimensions of resistance of the subaltern in shifting politico-cultural contexts. It also unfolds the structure of representation of the subaltern transformed within transitions which are observed more vehemently through the different politico-cultural scenarios of filmmaking, particularly before and after the Maoist insurgency. The last part analyses the aspects or efforts of the self-formation of the subaltern in terms of- along with class- caste, ethnicity and gender with references to representative Nepali movies, i.e. Numafung, Batomuniko Phool and Uma flash hope within hopelessness.